0315 On the Presence and Absence of Images - Lavinia Amenduni (RIHA Journal, 2024)
Starting from the presence of a painting by Aimé Morot among the slide collection of Charles Lang Freer, a collection otherwise devoted to modern American painters and Asian art, the essay traces back the origin of this slide to the collection of Ernest Fenollosa and untangles the documentation on how his slides found their home in the Freer Archives in Washington, D.C. Fenollosa’s use of this slide to juxtapose ancient Japanese art and modern French painting is a starting point for reflecting on the role that the presence – or absence – of images played in printed texts as opposed to lectures, and how that in turn fueled the tendency towards stylistic comparisons. Lastly, the position of lantern slides as a tool that was once indispensable to art history, and now, in the digital era, becomes a historical and material object to be studied as such, allows us to reflect on one of the many epistemological shifts that we face as art historians.